Revisão de Literatura do uso da Espécie vegetal Uncaria tomentosa na odontologia: Potencial aplicabilidade em pacientes do Sistema Único de Saúde (SUS) - Paes, Leticia Silva (2022)
Dental care is a topic of great relevance when it comes to the general well-being of man. In Brazil, oral health has gained more and more space in the country's public health scenario, although diseases such as caries, periodontal diseases, candidiasis, stomatitis and other oral manifestations of an inflammatory and infectious nature are still recurrent in the dental routine. In this scenario, one of the ways the dentist works in the management of these conditions is the prescription of medicines, with phytotherapy and the prescription of herbal medicines regulated by the Ministry of Health, inserted in the Unified Health System (SUS), and recognized by the Federal Council of Dentistry. Thus, the objective of this work was to carry out a bibliographic survey regarding the pharmacological activities of Uncaria tomentosa - known for its proven anti-inflammatory and immunoregulatory activity - and its potential applicability in dental practice , through a systematic review of the literature, without meta-analysis. For this, searches were carried out in the MedLine/PUBMED, Scopus and Web of Science databases, using the descriptors Uncaria tomentosa, cat's claw and dentistry, associated with the boolean operators OR and AND. After applying the search strategy, nine articles were selected for review. The bibliographic findings were favorable to the implementation of cat's claw in dental practice, due to the beneficial pharmacological potential of the plant being quite broad. In addition, its relevance to the SUS is also highlighted, with regard to prevention and health promotion, and optimization of the use of resources. However, more recent and more robust studies, such as randomized clinical trials, are needed to better support the proposed theme.